Rocket and spacecraft propulsion principles, practice and new developments - Turner, Martin J. L. 1942- (Springer-Praxis books in astronautical engineering., 2009)
The revised edition of this practical, hands-on book discusses the range of launch vehicles in use today throughout the world, and includes the very latest details of some of the advanced propulsion systems currently being developed. The author covers the fundamentals of the subject, from the basic principles of rocket propulsion and vehicle dynamics through the theory and practice of liquid and solid propellant motors, to new and future developments.